Viscoelastic behavior and physico-chemical characteristics of heated swai-fish (Pangasius hypophthalmus) based emulsion containing fermented soybeans - Techarang J. (2017)
© 2015 Elsevier Ltd. Various proportions of fermented soybeans i.e. thua nao and rice- koji miso were added into the swai-fish emulsion to improve the health potential of the products. Accordingly, the physico-chemical, microbiological properties and sensory attributes of the fish-based emulsions as well as the main ingredients were determined. The results showed that fatty acid profile of the swai-fish fillet consisted mainly of saturated and monounsaturated fatty acids, while isoflavone profiles of the fermented soybeans illustrated that thua nao contained more aglycones than rice- koji miso. For physical properties, the profiles of storage and loss moduli, creep parameters and gel strength depicted that samples added thua nao gave rise to stronger gel structure than those added rice- koji miso or the whole fish emulsion. Microbiological examination indicated that the fish emulsion with thua nao addition showed high total plate or spore counts.